Evaluasi Pelatihan Peningkatan Kompetensi Petugas Rekam Medis di Puskesmas Cangkol - Lina Khasanah; Gugun Priyadi (FORIKES, 2021)
One of the quality public health center a service will depend on the availability and competence of an agency’s human resources. The determination of training methods in improving the quality of resources is adapted to the situation and conditions of the organization. Cangkol health center is one of the public health center that does not have medical record administrators according to educational background. For this reason, the training is carried out using the demonstration and example and coaching models so that the material received is expected to be immediately applied in the workplace. This research uses descriptive qualitative and simple quantitative analysis. Data were collected directly in the form of a checklist questionnaire, observation and indepth interviews. Training evaluation uses up to three levels from Kirkpatrick’s four level covering reaction, learning and behaviour. From the results of this training, it was found that the process evaluation in the implementation of the training averaged 4.05 from a scale of 5 which indicated that the training implementation process was in the good category. The evaluation of the learning level results showed an increase seen from the average post-test result of 87.77which was greater than the pre-test result of 59.99. The evaluation of the results of the total behavior level averages 2.4 on a scale of 4. This shows that there has been no significant increase in on the job training interventions even though 2.4 is in the enough category. The conclusion from the training evaluation shows a fairly good improvement.Keywords: medical record; on the job training; Kirk PatrickABSTRAKKualitas suatu pelayanan di Puskesmas salah satunya akan tergantung dari ketersediaan dan kecakapan sumber daya manusia suatu instansi. Penentuan metode pelatihan dalam meningkatkan kualitas sumber daya disesuaikan dengan situasi dan kondisi organisasi. Puskesmas Cangkol merupakan salah satu Puskesmas yang tidak memiliki petugas rekam medis sesuai dengan latar belakang pendidikan. Untuk itu pelatihan yang dilakukan menggunakan on the job training yang menggunakan model Demonstration and Example dan Coaching sehingga materi yang diterima diharapkan bisa langsung diaplikasikan ditempat kerja. Penelitian ini menggunakan analisis kualitatif deskriptif dan kuantitatif sederhana. Pengambilan data dilakukan secara langsung baik dalam bentuk kuesioner checklist, observasi maupun wawancara mendalam. Evaluasi pelatihan menggunakan sampai tiga level dari empat level Kirkpatrick yang meliputi Reaction, Learning and Behaviour. Dari hasil pelatihan ini didapat Level 1 Reaction rata-rata 4,05 dari skala 5 yang menunjukkan bahwa proses pelaksanaan pelatihan berada pada kategori Baik. Level 2 Learning menunjukkan peningkatan dilihat dari rata-rata hasil post test 87,77 lebih besar dari hasil pre test 59,99. Pada level 3 Behaviour total rata-rata 2,4 pada skala 4. Hal ini menunjukkan bahwa pada hasil perilaku belum ada peningkatan yang signifikan terhadap intervensi pelatihan on the job training meskipun 2,4 termasuk kategori Cukup. Kesimpulan dari evaluasi pelatihan menunjukkan peningkatan efektifitas kualitas yang cukup baik.Kata kunci: rekam medis; on the job training; Kirk Patrick